RNA-seq Analysis of Cold and Drought Responsive Transcriptomes of Zea mays ssp. mexicana L. - Lu, Xiang; Zhou, Xuan; Cao, Yu; Zhou, Meixue; McNeil, David; Liang, Shan; Yang, Chengwei (Frontiers in Plant Science, 2017)
The annual Zea mays ssp. mexicana L. is a member of teosinte, a wild relative of the Zea mays spp. mays L. This subspecies has strong growth and regeneration ability, high tiller numbers, high protein and lysine content as well as resistance to many fungal diseases, and it can be effectively used in maize improvement. In this study, we reported a Zea mays ssp. mexicana L. transcriptome by merging data from untreated control (CK), cold (4℃) and drought (PEG2000, 20%) treated plant samples. A total of 251,145 transcripts (N50 = 1,269 bp) and 184,280 unigenes (N50 = 923 bp) were predicted, which code for homologs of near 47% of the published maize proteome. Under cold conditions, 2,232 and 817 genes were up-regulated and down-regulated, respectively, while fewer genes were up-regulated (532) and down-regulated (82) under drought stress,indicating that Zea mays ssp. mexicana L. is more sensitive to the applied cold rather than to the applied drought stresses. Functional enrichment analyses identified many common or specific biological processes and gene sets in response to drought and cold stresses. The ABA dependent pathway, trehalose synthetic pathway and the ICE1-CBF pathway were up-regulated by both stresses. GA associated genes have been shown to differentially regulate the responses to cold in close subspecies in Zea mays. These findings and the identified functional genes can provide useful clues for improving abiotic stress tolerance of maize.